Physical exercise for late-life major depression. (September 2015) - Murri, M. Belvederi; Amore, M.; Menchetti, M.; Toni, G.; Neviani, F.; Cerri, M.; Rocchi, M. B. L.; Zocchi, D.; Bagnoli, L.; Tam, E.; Buffa, A.; Ferrara, S.; et al.
Abstract : Background: Interventions including physical exercise may help improve the outcomes of late-life major depression, but few studies are available. Aims: To investigate whether augmenting sertraline therapy with physical exercise leads to better outcomes of late-life major depression. Method: Primary care patients (>65 years) with major depression were randomised to 24 weeks of higher-intensity, progressive aerobic exercise plus sertraline (S+PAE), lower-intensity, non-progressive exercise plus sertraline (S+NPE) and sertraline alone. The primary outcome was remission (a score of 10 on the Hamilton Rating Scale for Depression). Results: A total of 121 patients were included. At study end, 45% of participants in the sertraline group, 73% of those in the S+NPE group and 81% of those in the S+PAE group achieved remission ( P = 0.001). A shorter time to remission was observed in the S+PAE group than in the sertraline-only group. Conclusions: Physical exercise may be a safe and effective augmentation to antidepressant therapy in late-life major depression.